Non-invasive assessment of right ventriculo-arterial coupling in dilated cardiomyopathy – insights from 3D echocardiography. (25th November 2020) - Vijiiac, A.E; Guzu, C; Scarlatescu, A; Onciul, S; Iancovici, S; Petre, I; Zamfir, D; Pascal, A.M; Onut, R; Stoian, M; Dorobantu, M
Abstract: Background: Right ventricular-pulmonary artery coupling (RVPAC) reflects the mechanical efficiency of the interaction between the right ventricle (RV) and the pulmonary circulation unit. Although it has been traditionally assessed with right heart catheterisation (RHC), modern imaging techniques enable the non-invasive estimation of the RVPAC, which proved to correlate well with measurements derived from RHC. Methods: We used three-dimensional (3D) echocardiography to study 88 consecutive patients (60.4±13.4 years, 69 men) with dilated cardiomyopathy (DCM) and left ventricular ejection fraction<40% and we measured the RV volumes and RV ejection fraction (RVEF) using dedicated software. 15 healthy individuals served as controls. RVPAC was estimated non-invasively as the ratio between the RV end-systolic volume and stroke volume. Right-sided heart failure was defined as either elevated jugular venous pressure, pedal oedema or congestive hepatomegaly. Results: Patients with DCM showed larger RV end-diastolic volume (163±60.9 ml vs. 91.3±13.2 ml; p<0.0001), as well as larger RV end-systolic volume (97.3±43.2 ml vs. 39.8±7.2 ml; p<0.0001) than healthy controls. The patients in the study group showed lower RVEF: 41.5±8.5% vs. 56.5±3.6% (p<0.0001). Non-invasive RVPAC was 1.53±0.60 in DCM patients vs. 0.78±0.11 in controls (p<0.0001). RVPAC had an excellent negative correlation with RVEF, both in DCM patients (r=−0.96, p<0.0001) and in controls (r=−0.99, p<0.0001). Patients with no signs of right-sided heart failure had lower RVPAC (1.38±0.45) than patients with at least one sign of right heart failure (1.90±0.72, p=0.03). Patients with mild symptoms of heart failure (NYHA classes 1 or 2) showed lower RVPAC (1.37±0.48) than DCM patients with severe heart failure (NYHA classes 3 or 4): 1.79±0.68 (p=0.003). Conclusions: 3D echocardiography provides useful insights in the functional assessment of the cardiopulmonary unit. Non-invasive RVPAC is impaired in patients with DCM, and it is more impaired when signs of right-sided heart failure are present. Severe symptoms are associated with more pronounced decoupling of the RV and the pulmonary circulation. The prognostic significance of non-invasive RVPAC in a disease primarily involving the left ventricle remains to be clarified. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): This work was supported by CREDO Project - ID: 49182, financed through the SOP IEC -A2-0.2.2.1-2013-1 cofinanced by the ERDF